Prehranjevalne navade učencev drugega in tretjega triletja osnovne šole - Orthaber, Mateja (Revija za elementarno izobraževanje, 2011)
The fundamental elements of healthy eating for children and adolescents is a high-quality and varied diet that will help develop good habits for future life. Therefore, we presented some statistics on the eating habits of children and adolescents in elementary school and the organization of school meals in our country. The primary purpose of this study was to examine the basic characteristics of the eating habits of students. We included their opinions and attitudes toward eating at home and school according to age, gender and school. It appears that there are differences in eating habits, satisfaction with school meals and other nutritional issues among students of different gender, age and place of schooling.
Keywords: healthy nutrition; zdrava prehrana; prehranjevalne navade; eating habits; elementary schools; učenci; osnovne šole